Comparison of Friedewald, Martin/Hopkins, and Sampson formulae with direct LDL measurement in hyperlipidaemic and normolipidaemic adults: Comparison of Friedewald, Martin/Hopkins, and Sampson formulae with direct LDL measurement - Alpdemir, Medine; Alpdemir, Mehmet Fatih; Şeneş, Mehmet (Journal of Medical Biochemistry, 2024)
ABSTRACTObjective: In our study, we aimed to compare and validate the performance of the Friedewald, Martin/Hopkins, and Sampson formulae with direct LDL-C measurement.Material and Methods: The study was a retrospective investigation which by the Department of Medical Biochemistry of the Ankara Training and Research Hospital between 1 January 2021 and 31 December 2022. Our study evaluated the results of 6297 patients aged 18-99 years who underwent cholesterol panel TC, TG, HDL-C and direct LDL-C in our laboratory.   Estimated LDL-C calculated according to Friedewald, Martin/Hopkins, and Sampson formulae. Results: All three formulae showed a stronger positive correlation with d-LDL-C (0.905, 0.897, and 0.886, respectively, for all data, p
Keywords: Martin/Hopkins; Sampson; Friedewald; Low-density lipoprotein